Relationship between neurotoxic kynurenine metabolites and reductions in right medial prefrontal cortical thickness in major depressive disorder - Meier, Timothy B.; Drevets, Wayne C.; Wurfel, Brent E.; Ford, Bart N.; Morris, Harvey M.; Victor, Teresa A.; Bodurka, Jerzy; Teague, T. Kent; Dantzer, Robert; Savitz, Jonathan (Brain, behavior, and immunity, 2016)
•Thickness of right BA24 and right BA32 was reduced in major depressive disorder.•Serum KynA/3HK and KynA/QA was reduced in MDD.•CRP was inversely associated with BA32 thickness.•KynA/3HK partially mediated the relationship between CRP and thickness of BA32. Reductions in gray matter volume of the medial prefrontal cortex (mPFC), especially the rostral and subgenual anterior cingulate cortex (rACC, sgACC) are a widely reported finding in major depressive disorder (MDD). Inflammatory mediators, which are elevated in a subgroup of patients with MDD, activate the kynurenine metabolic pathway and increase production of neuroactive metabolites such as kynurenic acid (KynA), 3-hydroxykynurenine (3HK) and quinolinic acid (QA) which influence neuroplasticity. It is not known whether the alterations in brain structure and function observed in major depressive disorders are due to the direct effect of inflammatory mediators or the effects of neurotoxic kynurenine metabolites. Here, using partial posterior predictive distribution mediation analysis, we tested whether the serum concentrations of kynurenine pathway metabolites mediated reductions in cortical thickness in mPFC regions in MDD. Further, we tested whether any association between C-reactive protein (CRP) and cortical thickness would be mediated by kynurenine pathway metabolites. Seventy-three unmedicated subjects who met DSM-IV-TR criteria for MDD and 91 healthy controls (HC) completed MRI scanning using a pulse sequence optimized for tissue contrast resolution. Automated cortical parcellation was performed using the PALS-B12 Brodmann area atlas as implemented in FreeSurfer in order to compare the cortical thickness and cortical area of six PFC regions: Brodmann areas (BA) 9, 10, 11, 24, 25, and 32. Serum concentrations of kynurenine pathway metabolites were determined by high performance liquid chromatography (HPLC) with tandem mass spectrometry (MS/MS) detection, while high-sensitivity CRP concentration was measured immunoturbidimetrically. Compared with HCs, the MDD group showed a reduction in cortical thickness of the right BA24 (p<0.01) and BA32 (p<0.05) regions and MDD patients with a greater number of depressive episodes displayed thinner cortex in BA32 (p<0.05). Consistent with our previous findings in an overlapping sample, the KynA/3HK ratio and the log KynA/QA were reduced in the MDD group relative to the HC group (p’s<0.05) and symptoms of anhedonia were negatively correlated with log KynA/QA in the MDD group (p<0.05). Both KynA/3HK and log KynA/QA at least partially mediated the relationship between diagnosis and cortical thickness of right BA32 (p’s<0.05). CRP was inversely associated with BA32 thickness (p<0.01) and KynA/3HK partially mediated the relationship between CRP and the thickness of right BA32 (p<0.05). The results raise the possibility that the relative imbalance between KynA and neurotoxic kynurenine metabolites may partially explain the reductions in mPFC thickness observed in MDD, and further that these changes are more strongly linked to the putative effects of neuroactive kynurenine metabolites than those of inflammatory mediators.